HEGEMONI KEKUASAAN DALAM SEBUAH NOVEL ANIMAL FARM KARYA GEORGE ORWELL - Samsul Arifin Arifin; Sugiantoro; Rudi Antonius Antonius (Metalanguage: Jurnal Ilmu Bahasa dan Sastra Indonesia, 2022)
This study aims to understand the structure contained in George Orwell's Animal Farm novel and find out the various forms of hegemony in it. This type of research is qualitative descriptive using the sociological theory of literature. The data analysis technique was carried out by (1) identifying the data obtained from George Orwell's Novel Animal Farm (2) Classifying the data according to the hegemony of power contained in the Animal Farm area. (3) Analyze in the form of a description. (4) Summing up the results. (5) Writing a research report. The results of this study the structure of George Orwell's Novel Animal Farm describes the upper and lower social classes which involve the social background of the life of the characters. The upper social class consists of pigs, servants and followers of pigs (other than pigs). Whereas in the lower social class, namely the common people (other animals as ordinary citizens in a livestock environment). In the second result, there are 2 types of hegemony, namely domination by violence and ideological hegemony in a subtle way through various thoughts to incite others through words that can hegemony others so that other people will not realize that they are is in hegemony.